Character Building in Lang Leav Poetry “Sea of Strangers” - Nadrotin Mawaddah; Mutmainnah Mustofa; Solihatul Ulya; Abdul Moueed (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2021)
This research aims at analyzing the character building of selected poetries in Lang Leav’s “Sea of Strangers”. In this research, a qualitative approach is used as the research design, and the data was analyzed using content analysis. “Sea of Strangers” is a continuation of Lang Leav book series Love & Misadventures, Lullabies, and The Universe of Us. There were eight poetries analyzed and several character buildings found in those poetries. The character buildings that appear are the character of patient, hard-working, religious, strong, creative, independent, confident, being realistic, respectful, honest, caring, and loving. From the eight poetries analyzed, almost all of those poetries explained the women's strength when they feel the pain of heartbreaking, waiting, romance, and insight into everyday life. Besides the beauty of the words used by the writer, these poetries also contain a lot of inspiring messages.